Pengaruh Customer Relationship Marketing Dan Konten Marketing Terhadap Minat Beli Konsumen - Mayurina Dwita (Jurnal Akuntansi, Manajemen dan Ekonomi Digital, 2022)
The problem in this research is to examine the influence of customer relationship marketing on consumer buying interest, the effect of marketing content on consumer buying interest and the influence of customer relationship marketing and marketing content on consumer buying interest at PT. Yumeida Utama Medan. The research method used is the associative method. Associative research is research that aims to determine the relationship between two or more variables. In this study using as many as 88 respondents. The results of the study using the t-test (partial) t-count customer relationship marketing (X1) obtained 2.055 > t-table = 1.66298. These results concluded that the variable customer relationship marketing partially has a positive and significant influence on consumer buying interest at PT. Yumeida UtamaMedan. The results of the study using the t-test (partial) t-count marketing content (X2) obtained with a value of 2.834 > t-table = 1.66298, namely the marketing content variable partially has a positive and significant influence on consumer buying interest at PT. Yumeida UtamaMedan. The results of the study using the F-test, the F-count value of customer relationship marketing (X1) and content marketing (X2) was obtained at 4.687 > F-table = 3.10, then customer relationship marketing (X1) and content marketing (X2) together (simultaneously) have a positive and significant influence on consumer buying interest at PT. Yumeida Utama Medan. Keywords: customer relation marketing, content marketing, consumers, associative method